Penerapan Sistem Antrian Dengan Simulasi Model Menggunakan Software Promodel Di PT.Retail Berkah - Gumelar, Gugum; Darajatun, Rizki Achmad (Patria Artha Technological Journal, 2021)
In the current era of globalization, the industrial world is developing very rapidly both the service industry and the product industry in this case time is very important especially for service providers, so the company must be able to maintain its existence by limiting service time so that companies can meet targets many services to the customer. Queues can be found in several public service facilities where the community or goods will experience a queuing process from the arrival process, entering the queue and waiting, until the service process lasts until the end of service. The purpose of queuing analysis is to minimize customer waiting and service capacity cost. The model is a representation of a simplified real system. the model is a very useful tool for analyzing and designing systems. Simulation is a methodology for carrying out experiments using models from a real system by creating a simulation model of a system so it is expected to be easier to do the analysis. Promodel stands for Production Modeler is an application issued by Promodel company. This application serves to simulate or model various types of manufacturing and service systems. These manufacturing systems such as shops, conveyors, assemblies, just-in-time systems, flexible manufacturing systems can all be modeled with promodels. The time used in this case is quite good, namely at counter 1 of 49.67, counter 2 of 40.57 and counter 3 of 33.24. Because time is very important, especially for service providers, companies must be able to maintain their existence by limiting service time so that companies can meet the target number of services to customers.